Confidence in Social Relationships of Roleplay Users in the Sidoarjo Roleplay Community: Kepercayaan Diri Berelasi Sosial Pengguna Roleplay di Komunitas Roleplay Sidoarjo - Widyatiari, Lita Salma; Ansyah, Eko Hardi (Indonesian Journal of Innovation Studies, 2023)
Humans are social creatures so humans must have relationships. To have relationships, individuals must have self-confidence. Self-confidence is a belief in one's own abilities that can make individuals confident and responsible in their actions. This research is motivated by kpop roleplay users who have differences in showing confidence in relationships on social media. The purpose of this study is to reveal the description of aspects and factors of self-confidence in relationships. this research uses a qualitative type with a phenomenological approach. data collection method used is interviews. The results of this study indicate that the three users were able to show their confidence. Factors that influence the formation of self-confidence are physical appearance, self-concept and relationships with peers.